O perfil do produtor teatral em Maceió: características da profissão nos grupos de teatro atuantes em 2013 - Rodrigues, Anna Christina de Queiroz (2014)
The research aims to examine questions relating to cultural production of theater groups working in Maceió at 2013 and the profile of its producer. His main focus was to understand the formation processes of these different producers and their professional careers, raising, finally, what are the production models of theater groups in the metropolis. To account for the diversity, the first step was to situate the cultural production and political theater in Brazil. After, its constructed a theater maceioense analysis from the current situation of theatrical spaces and their groups. Then trace the perspective of groups, analyze how they deal with the production of their shows and that professional is responsible for this activity. Therefore, interviews, oral histories of working life, with representatives of theater groups or their producers were performed. During the research, it was found that there are two forms of production in Maceio groups: the first is represented by groups having only producers, even acting on other functions besides the production. In second, the groups work with collective or shared production, dividing production functions between all its components. The reality presented in this dissertation is often the result of the dedication of these individuals more to the theater than what is written in the books production. The final considerations bring the possibility of further research, given that the theater group or other productions in Maceió, is still a field full of possibilities and theatrical production tool as well.